Transcriptome Sequencing Analysis of Peripheral Blood of Type 2 Diabetes Mellitus Patients With Thirst and Fatigue - Lv, Bohan; Bao, Xueli; Li, Ping; Lian, Juan; Wu, Yanxiang; An, Tian; Zhang, Jing; Yang, Xiuyan; Wang, Tingye; Zhu, Jiajian; Hu, Yuanyuan; Jiang, Guangjian; et al. (Frontiers in Endocrinology, 2020)
Purpose: The purpose of this study is to explore the differences in transcriptome expression profiles between healthy subjects and type 2 diabetes mellitus patients with thirst and fatigue (D-T2DM). In addition, to investigate the possible role of non-coding RNAs in the pathogenesis of D-T2DM. Methods: In this research, we constructed the expression profiles of RNAs by RNA sequencing in the peripheral blood of D-T2DM patients and healthy subjects. Afterwards, a series of bioinformatic analysis of differentially expressed RNAs were carried out. Results: Compared with healthy subjects, a total of 469 mRNAs, 776 long non-coding RNAs (lncRNAs) and 21 circular RNAs (circRNAs) were differentially expressed in D-T2DM patients. Furthermore, several genes associated with insulin resistance, inflammation and mitochondrial dysfunction have been identified in differentially expressed mRNAs. Differentially expressed lncRNAs is primarily involved in biological processes associated with immune responses. In addition, differentially expressed circRNAs can act by targeting miRNAs associated with glucose metabolism and mitochondrial function. Conclusions: Our results may bring a new perspective on the pathogenesis of D-T2DM and promote the development of novel treatments for this disease.